PERILAKU PENCEGAHAN PENULARAN TUBERKULOSIS: TINJAUAN ASPEK INDIVIDU - Rusdin Wally; Sulistiyani Sulistiyani; Luluk Cahyanti; Alif Nurul Rosyidah (Ensiklopedia Research and Community Service Review, 2026)
Pulmonary tuberculosis remains one of the global public health problems, especially in developing countries. Based on document searches and routine health reports, the Sumbersari Community Health Center is recorded as one of the health centers with the highest number of tuberculosis cases in East Java Province. The purpose of this study was to determine the relationship between individual aspects and the prevention of tuberculosis transmission. A cross-sectional study design was used in this study. The study was conducted in the working area of the Sumbersari Community Health Center. The study was conducted in October 2025. The study population consisted of tuberculosis patients in the working area of the Sumbersari Community Health Center. The sample consisted of 60 respondents. The sampling technique used was total sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between knowledge (p value: 0.003) and family support (p value: 0.043) and the prevention of tuberculosis transmission. It is recommended that health center staff and health cadres investigate contacts within families to provide health education on the prevention of tuberculosis transmission among family members. Keywords: Family Support, Knowledge, Tuberculosis.